STRUCTURE DESIGN AND STRENGTH ANALYSIS OF THE SLIDER OF A ROCKET PROJECTILE - YUE XiaoHong; WANG JunPing; LI ShunLi; HUANG HanJun; LV Jian (Jixie qiangdu)
Slider is one of the main parts of a rocket projectile,which determines the stability and safety of a rocket launch. A slider structure design that satisfies the suspended-type launch was introduced in this research. Based on the theoretical analysis of offtrack speed and time,the slider structure was designed. By using numerical simulations,the strength of front slider under two different situations,ontrack and offtrack,was checked. The results show that the strength of slider meets the design requirement. The designed slider was applied to a rocket projectile flying test and the design feasibility was verified.